MALE DIRECTORS CONTRIBUTING TO WOMEN EMANCIPATORY CINEMA: A PENTADIC ANALYSIS OF TWO INDIAN FILMS - Sharma, Karuna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
With filmmaking being democratized, social imperatives are becoming central theme in cinema. In the Indian context, cinematic narratives are now trying to be inclusive of issues of importance. There are instances where men have offered stories and narratives that profoundly depict issues related to women. These instances, though limited, yet demand an academic attention. This paper analyses two films that portray gender issues; one Malayalam and the other, Hindi, both released on OTT platforms Neestream and Amazon respectively. It investigates the constructive elements in both the narratives employed by the filmmakers, both men, to underline the silent patriarchy existing in the society.